Visuo-haptic transfer for object recognition in children with periventricular leukomalacia and bilateral cerebral palsy. Issue 8 (17th November 2019) - Purpura, Giulia; Perazza, Silvia; Cioni, Giovanni; Tinelli, Francesca
ABSTRACT: Object recognition is a complex adaptive process that can be impaired in children with neurodevelopmental disabilities. Recently, we found a significant effect of time on the development of unimodal and crossmodal recognition skills for common objects in typical children and this was a starting point for the study of visuo-haptic object recognition skills in impaired populations. In this study, we investigated unimodal visual information, unimodal haptic information and visuo-haptic information transfer in 30 children, from 4.0 to 10.11 years of age, with bilateral Periventricular Leukomalacia (PVL) and bilateral cerebral palsy. Results were matched with those of 116 controls. Participants were tested using a clinical protocol, adopted in the previous study, involving visual exploration of black-and-white photographs of common objects, haptic exploration of real objects and visuo-haptic transfer of these two types of information. Results show that in the PVL group as in controls, there is an age-dependent development of object recognition abilities for visual, haptic and visuo-haptic modalities, even if PVL children perform worse in all the three conditions, in comparison with the typical group. Furthermore, PVL children have a specific deficit both in visual and haptic information processing, that improves with age, probably thanks to everyday experience, but the visual modality shows a better and more rapid maturation, remaining more salient compared to the haptic one. However, multisensory processes partially facilitate recognition of common objects also in PVL children and this finding could be useful for planning early intervention in children with brain lesion.